Hubungan Kerjasama Orangtua dengan Guru Pendidikan Agama Kristen dalam Meningkatkan Minat Belajar PAK Siswa Kelas XI SMA Swasta HKBP Doloksanggul Kabupaten Humbang Hasundutan Tahun Ajaran 2024/2025. - Eka Yolanda Siregar; Lustani Samosir; Goklas J Manalu; Elisamark Sitopu; Rotua Samosir (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The purpose of this study was to determine whether there is a relationship between Parental Cooperation and Christian Religious Education Teachers in Increasing Interest in Learning PAK of Grade XI Students of HKBP Doloksanggul Private High School, Humbang Hasundutan Regency in the 2024/2025 Academic Year. The research hypothesis is that there is a positive and significant relationship between Parental Cooperation and Christian Religious Education Teachers in Increasing Interest in Learning PAK of Grade XI Students of HKBP Doloksanggul Private High School, Humbang Hasundutan Regency in the 2024/2025 Academic Year. This study uses a quantitative descriptive inferential approach, with a population of 159 people and a sample of 32 people, which is 20% of the population. Data were collected with a closed questionnaire of 28 items. The results of the analysis show that there is a positive and significant relationship between Parental Cooperation and Christian Religious Education Teachers in Increasing Interest in Learning PAK of Grade XI Students of HKBP Doloksanggul Private High School, Humbang Hasundutan Regency in the 2024/2025 Academic Year. This is proven by r count > r table of 0.804 > 0.349 and t count > t table of 7.387 > 2.042, thus there is a significant relationship between variable X and variable Y. So Ha is accepted and Ho is rejected.